Moving from Disciplinarity to Transdisciplinarity in the Service of Thrivable Systems. (9th September 2014) - Rousseau, David; Wilby, Jennifer
<x xml:space="preserve">Abstract</x> In 2011 Jennifer Wilby proposed a new framework for viewing the philosophy, principles and practice of systems thinking, in furtherance of research and practice into transdisciplinary forms of intervention. This new framework reveals the effect of the interactions between systems principles and system structure in producing complex systems behavior, demonstrates why such methodologies are classed as systemic and anticipates how these systemic methodologies can be used to support transdisciplinarity in exploration, design and management. In this light Alexander Laszlo's call for building a thrivable global system, presented at the 57th Conference of the ISSS, represents a concrete example of the problems and opportunities foreseen in the general call Wilby made in 2012 for developing and using transdisciplinary methods that can nurture complex systems to function effectively and harmoniously. Exploring the underpinning philosophy, principles and practice for a new era of systemic intervention that meets the challenges of the Anthropocene is the aim of the work presented in this paper, focused on linking the transdisciplinary nature of thrivable systems with the development of transdisciplinary systems research and practice. Copyright © 2014 John Wiley & Sons, Ltd.